COMPARISON OF MUSICAL AND CULTURAL ACTIVITIES OF SERBIAN CULTURAL SOCIETIES IN SLOVENIA AND SLOVENIAN IN SERBIA (Heritage, 2021)
A surprisingly small number of papers dealing with the activity of cultural communities of Serbs in Slovenia and cultural societies of Slovenians in Serbia can be found in the research that primarily investigates promotion and preservation of cultural heritage of these two peoples. The aim of the paper is to show the activities of these two minor communities, focused on promotion and preservation of own musical heritage within cultural societies where they act. Using the methodology of oral interviewing of leading people in cultural communities, significant research data were obtained related to study of importance of various aspects of investigation in minor ethnical communities.  By comparing the results provided by research in these two national minorities, organized in different cultural societies (i.e. in different countries), we wanted to investigate the relationship between minorities and cultural heritage as well as various aspects of its identification, promotion and transmission. In our paper we found that Serbian cultural societies in Slovenia primarily promoted the folklore tradition, while Slovenian cultural societies in Serbia were engaged in choir singing as their basic activity. The findings of research reveal significant possibilities for further ethno-musicological and musicological investigation combined with other scientific disciplines related to this topic.
Keywords: Cultural societies, minorities, Serbs in Slovenia, Slovenians in Serbia, folklore music